Leaching kinetics of scheelite with sodium phytate - Zhu, Xinrui; Liu, Xuheng; Zhao, Zhongwei (Hydrometallurgy, 2019)
Considering the environmental requirements and cost of energy consumption, organic phytic acid salt, a non-toxic and non-polluted green reagent, was used to decompose scheelite. The present study investigated the leaching kinetics of scheelite ore with sodium phytate. The effects of reaction temperature, initial sodium phytate concentration, scheelite ore particle size, and stirring speed on the scheelite leaching rate were analyzed. While independent of stirring speed, it was found that the leaching rate was significantly influenced by the temperatures and particle sizes at the investigated range. The leaching data revealed that the effects of the relevant operating variables on leaching rates are consistent with the shrinking-core model, with internal diffusion being the rate-controlling step. The apparent activation energy based on the Arrhenius expression was calculated as 84.54 kJ/mol, and the kinetic equation associated with the leaching rate of scheelite was established using quadratic regression. •A green reagent sodium phytate is proposed for decomposition of scheelite.•The leaching kinetics is investigated based on unreacted shrinking core model.•The decomposition reaction of scheelite is controlled by internal diffusion.•The SEM results clearly demonstrate the internal diffusion mechanism.